Learning Outcomes Acquisition in Second Language Tertiary Education Classroom Practices (Global Journal of Human-Social Science, 2021)
Indeed, Learning Outcomes (LO) are vital components of a curriculum design. These themes are not only a reflex of Education academic, administrative standards but, more importantly, a prelude for lecturing's guidance and learning comprehension. Although Learning Outcomes refer to those learning achievements that learners will be able to demonstrate once completing the learning process, fulfilling this wanted goal still represents an academic challenge for all kinds of teaching and learning disciplines, and language is not exempted from being a subject that requires especial scrutinizes when addressing Learning Outcomes. Herewith, the study aimed to analyze learning outcome aspects and implications in second language acquisition in Tertiary Education classroom practices. It also brings up a based prospect on language insights and curriculum settings. To accomplish this objective, various manuscripts and Internet accredited websites were searched. The outcome revealed that the idea of boosting second language learners' knowledge and skills cognition meaning, differentiation, and association to treat the acquisition of learning outcomes at Tertiary Education classroom practices might be assumed as an academic functional approach that helps academicians in handling the second language acquisition process, and therefore in producing university graduate's skills.
Keywords: linguistics; learning outcomes; assignments; evaluation criteria